2012
DOI: 10.1037/a0027764
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal relations between self-critical perfectionism and depressive symptoms: Evidence from a short-term, four-wave longitudinal study.

Abstract: Is self-critical perfectionism an antecedent of depressive symptoms, a consequence of depressive symptoms, or both? In the present study, self-critical perfectionism (i.e., harsh criticism of one's actions, negative reactions to perceived failures, and extreme concerns over others' evaluations) and depressive symptoms were conceptualised as a unified, interlocking syndrome wherein self-critical perfectionism and depressive symptoms reciprocally influence each other over time. This reciprocal relations model wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
58
0
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 82 publications
(73 citation statements)
references
References 68 publications
9
58
0
6
Order By: Relevance
“…En lo que respecta a las diferencias en función de la edad, no se observaron divergencias significativas entre los participantes que puedan ser atribuibles a su edad, tal y como se predijo en la Hipótesis 2 y en consonancia con la literatura previa al respecto, la cual ha defendido que aunque es posible encontrar ligeras fluctuaciones con los años, el perfeccionismo es un rasgo de la personalidad bastante estable en el tiempo (Damian et al, 2013;Herman et al, 2013;Maia et al, 2011;McGrath et al, 2012;Sherry et al, 2013;Soenens et al, 2008). Asimismo, y en consonancia con la Hipótesis 3, no se observaron efectos de interacción sexo x curso en ninguna de las dimensiones perfeccionistas evaluadas.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…En lo que respecta a las diferencias en función de la edad, no se observaron divergencias significativas entre los participantes que puedan ser atribuibles a su edad, tal y como se predijo en la Hipótesis 2 y en consonancia con la literatura previa al respecto, la cual ha defendido que aunque es posible encontrar ligeras fluctuaciones con los años, el perfeccionismo es un rasgo de la personalidad bastante estable en el tiempo (Damian et al, 2013;Herman et al, 2013;Maia et al, 2011;McGrath et al, 2012;Sherry et al, 2013;Soenens et al, 2008). Asimismo, y en consonancia con la Hipótesis 3, no se observaron efectos de interacción sexo x curso en ninguna de las dimensiones perfeccionistas evaluadas.…”
Section: Discussionunclassified
“…El perfeccionismo se considera como un rasgo de la personalidad relativamente estable a lo largo del tiempo, tal y como han evidenciado recientemente diversos estudios longitudinales (e. g., Damian, Stoeber, Negru y Baban, 2013;Herman, Wang, Trotter, Reinke y Ialongo, 2013;Maia et al, 2011;McGrath et al, 2012;Sherry et al, 2013;Soenens et al, 2008). Por ejemplo, Maia et al (2011) evaluaron la estabilidad relativa del PSP y PAO a través de tres medidas separadas por intervalos anuales.…”
Section: Diferencias En Los Niveles De Psp Y Pao En Función De La Edadunclassified
See 1 more Smart Citation
“…Moreover, most of our knowledge about depression and perfectionism stems from the adult literature which suggests that perfectionism is a vulnerability, or risk factor, for depression (vulnerability model; Hewitt, Flett, & Ediger, 1996;Sherry, DEPRESSION AND PERFECTIONISM IN CHILDHOOD 4 Mackinnon, Macneil, & Fitzpatrick, 2012). There are, however, some studies that have demonstrated that perfectionism can also be an outcome of depression (scar model; Cox & Enns, 2003), or shares a reciprocal relationship with depression (reciprocal-causality model;McGrath et al, 2012). In the present study, we examined the temporal sequence between depressive symptoms and perfectionism in children approximately 12 years of age at T1 over three years in order to assess which model (vulnerability, scar, or reciprocal-causality) best explained the relationship between depressive symptoms and perfectionism.…”
Section: Longitudinal Links Between Perfectionism and Depression In Cmentioning
confidence: 99%
“…For the reason that perfectionism studies often conceptualizes the relationship between perfectionism and depression through the vulnerability standpoint, the research design and statistics used may be predetermined to fit with the model (McGrath et al, 2012). That is, while these studies support the model, they have not tested it specifically nor compared it to the DEPRESSION AND PERFECTIONISM IN CHILDHOOD 9 competing models (scar and reciprocal-causality models), rather most have just assumed that this was the case (with the exception of Sherry et al, 2012 andMcGrath et al, 2012). Hence, the competing models have often been overlooked.…”
Section: Vulnerability Modelmentioning
confidence: 99%